Fluorescence study of effect of particle size in PS latex/Al2O3 nanocomposite films. (14th May 2015) - Uğur, Ş.; Selin Sunay, M.; Pekcan, Ö.
Abstract : Steady state fluorescence and BioUV-Visible techniques were used to study film formation of polystyrene (PS) latex and Al2 O3 composites depending on PS particles size and Al2 O3 content. Two film series (SmPS/Al2 O3 and LgPS/Al2 O3 ) were prepared covering PS sphere (SmPS: 203 nm; LgPS: 382 nm) templates with various layers of Al2 O3 by dip coating method. The film formation behaviours of composites were studied by annealing them at a temperature range of 100–250°C and monitoring the scattered ( I sc ), fluorescence ( I P ) and transmitted ( I tr ) light intensities after each annealing step. The results indicate that LgPS/Al2 O3 films underwent complete film formation independent of Al2 O3 content while no film formation occurred above a certain Al2 O3 content for SmPS/Al2 O3 . Extraction of PS produced ordered porous structures for high Al2 O3 content in both series. Scanning electron microscopy images showed that the pore size and porosity could be easily tailored by varying PS particle size and Al2 O3 content.